Cambio generacional en las relaciones de género y poder de mujeres rurales : el caso de Sotaquirá, Boyacá (2017)
The current social dynamics in Colombia have led to the transformation of the role of women in rural and urban contexts and the opening of new opportunities for their participation in different economic activities and social scenarios. In order to understand the changes in the power and gender relation at the rural scenario and its relation with the transformations of its social and economic context, a qualitative research was carried out with an intergenerational look around the situation of the women in the municipality of Sotaquirá in Boyacá. This research project deepened in the aspects of participation in the educational and labor field, use of the time, participation in social organizations and capacity of negotiation and decision were deepened. As a result of the research, processes of empowerment between generations have been found, as well as new dynamics that have contributed to the exercise of rural woman agency.--Tomado del Formato de Documento de Grado.